A novel super frame Flexible Macroblock Ordering scheme for H.265 video transmission with unequal error protection - Indoonundon Deevya; Fowdur Tulsi Pawan; Soyjaudah Sunjiv (Serbian Journal of Electrical Engineering)
One of the most popular video coding standards in use today is High Efficiency Video Coding (HEVC), also known as H.265. In this paper, a novel Flexible Macroblock Ordering (FMO) scheme known as Super frame FMO (SFMO) is proposed for HEVC video compression. The SFMO scheme is combined with a concealment aware Unequal Error Protection (UEP) scheme using RS codes and interleaved to improve the performance of the RS decoder. Moreover, Multiple Description Coding (MDC) is used to further improve its performance. The simulation results have shown that the proposed system surpassed an Equal Error Protection (EEP) scheme by an average gain of 3.02 dB in the range of 0.1 £ Packet Loss Rate £ 0.5 with FLI (Frame Level Interleaving)- SFMO. Additionally, the FLI-SFMO scheme outperformed Explicit Chessboard- Wipe (ECW) FMO by an average gain of 1.48 dB.